Increased expression of inducible co-stimulator on CD4+ T-cells in the peripheral blood and synovial fluid of patients with failed hip arthroplasties. Issue 2 (February 2016) - Revell, P. A.; Matharu, G. S.; Mittal, S.; Pynsent, P. B.; Buckley, C. D.; Revell, M. P.
Abstract : Objectives: T-cells are considered to play an important role in the inflammatory response causing arthroplasty failure. The study objectives were to investigate the composition and distribution of CD4+ T-cell phenotypes in the peripheral blood (PB) and synovial fluid (SF) of patients undergoing revision surgery for failed metal-on-metal (MoM) and metal-on-polyethylene (MoP) hip arthroplasties, and in patients awaiting total hip arthroplasty. Methods: In this prospective case-control study, PB and SF were obtained from 22 patients (23 hips) undergoing revision of MoM (n = 14) and MoP (n = 9) hip arthroplasties, with eight controls provided from primary hip osteoarthritis cases awaiting arthroplasty. Lymphocyte subtypes in samples were analysed using flow cytometry. Results: The percentages of CD4+ T-cell subtypes in PB were not different between groups. The CD4+ T-cells in the SF of MoM hips showed a completely different distribution of phenotypes compared with that found in the PB in the same patients, including significantly decreased CD4+ T-central memory cells (p < 0.05) and increased T-effector memory cells (p < 0.0001) in the SF. Inducible co-stimulator (ICOS) was the only co-stimulatory molecule with different expression on CD4+ CD28+ cells between groups. In PB, ICOS expression was increased in MoM (p < 0.001) and MoP (p < 0.05) cases compared with the controls. In SF, ICOS expression was increased in MoM hips compared with MoP hips (p < 0.05). Conclusions: Increased expression of ICOS on CD4+ T-cells in PB and SF of patients with failed arthroplasties suggests that these cells are activated and involved in generating immune responses. Variations in ICOS expression between MoM and MoP hips may indicate different modes of arthroplasty failure. Cite this article: Professor P. A. Revell. Increased expression of inducible co-stimulator on CD4+ T-cells in the peripheral blood and synovial fluid of patients with failed hip arthroplasties. Bone Joint Res 2016;5:52–60. doi: 10.1302/2046-3758.52.2000574